A chloride-doped silver-sulfide cluster [Ag148S26Cl30(CCBut)60]6+: hierarchical assembly, enhanced luminescence and cytotoxicity to cancer cells. Issue 5 (21st January 2022) - Jiang, Zhan-Guo; Wu, Wei-Hong; Jin, Bo-Xing; Zeng, Hui-Min; Jin, Zhi-Gang; Zhan, Cai-Hong
Abstract : An unprecedented luminescence [Ag148 S26 Cl30 (C}CBu t )60 ](SbF6 )6 exhibits a hierarchical structure and induces the apoptosis of cancer cells. Abstract : The formation of high-nuclear silver(i ) clusters remains elusive and their potential applications are still underdeveloped. Herein, we report an unprecedented gigantic Ag148 ([Ag148 S26 Cl30 (C}CBu t )60 ](SbF6 )6 ) cluster co-templated by Cl − and S 2−, which was well-defined by single-crystal X-ray diffraction and high-resolution mass spectrometry. The cluster exhibits a hierarchical structure consisting of fused Ag24 X16 kernel, Ag60 X20 shell and "cluster of clusters assembling" of four pentagonal concave polyhedral Ag16 X5 units. Furthermore, the silver cluster emits red light at room temperature with a prominent 39.6% QY. The cellular uptake and cytotoxicity indicate that Ag148 induces apoptosis of cancer cells in a dose-dependent manner.